Feasibility analysis of free space earth to satellite optical link in tropical region - Norhanis, Aida; Islam, Md. Rafiqul; Wajdi, Al Khateeb (IIUM Press, 2011)
Free Space Optics (FSO) becomes a great attention because of the chances in transmitting data up to 2.5Gbps. There are a lot of advantages offered by FSO such as easily deployment with saving time and cost and no electromagnetic interference. In spite of the advantages, FSO has an uncontrolled drawback which is highly sensitive to atmospheric phenomena because uses air as tranmission medium. Current studies and researches are only focusing on FSO terrestrial link with short path length and based on data from temperate region. Therefore, this paper is aiming to provide feasibility analysis of FSO link from earth to satellite especially Low Earth Orbit (LEO) based on atmospheric data in tropical region. The analysis will include the losses from geometrical attenuation, absorption, scintillation, haze attenuation, and rain attenuation.